An Astrobiological Experiment to Explore the Habitability of Tidally Locked M-Dwarf Planets. Issue Volume 8:Issue S293(2012) (29th April 2014) - Angerhausen, Daniel; Sapers, Haley; Simoncini, Eugenio; Lutz, Stefanie; Alexandre, Marcelo da Rosa; Galante, Douglas
Abstract: We present a summary of a three-year academic research proposal drafted during the Sao Paulo Advanced School of Astrobiology (SPASA) to prepare for upcoming observations of tidally locked planets orbiting M-dwarf stars. The primary experimental goal of the suggested research is to expose extremophiles from analogue environments to a modified space simulation chamber reproducing the environmental parameters of a tidally locked planet in the habitable zone of a late-type star. Here we focus on a description of the astronomical analysis used to define the parameters for this climate simulation.